(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
The objective of this study was to conduct in-vitro quality control testing of brand versus generics of amlodipine tablets. One brand and two generic amlodipine tablets were used in the study. In the terms of weight variation, Brand, Generic A and Generic B have an above the mean weight limit variation of 2.15%, 2.23%, & 1.43% respectively. The lower mean weight limit variations are 1.85%, 1.92% & 1.23% respectively which are within the 7.5% standard limit of IP. Friability test shows that Brand, Generic A & Generic B have an average friability of 0.5%, 0.480% ,0.3% mass loss, which are within 1%. mass lost limit of IP. Hardness test shows that Brand, Generic A & Generic B have an average hardness of 0.9 kg/cm2, 2.3 kg/cm2 and 1 kg/cm2 respectively. The disintegration test shows that Brand, Generic A & Generic B fall within 15-minutes time interval segment with disintegration time determined 20 sec, 3 min, 2.5 min respectively. In terms of drug assay brand, Generic A & Generic B fall under IP limit of 90% to 110%. The Brand, Generic A & Generic B have a drug dissolution percentage of 101%, 104%, 104% respectively within 30 minutes sampling time interval. The QC tests results for amlodipine tablets show that Brand, Generic A and Generic B confirm to the IP standards.